2021
DOI: 10.1016/j.injury.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term differences in clinical prognosis between crossed- and parallel-cannulated screw fixation in vertical femoral neck fractures of non-geriatric patients

Abstract: Background and Purpose: Vertical femoral neck fractures (VFNFs) are one of the most difficult fractures to stabilize, with high non-union (17%), avascular necrosis (AVN, 21%), and femoral neck shortening (FNS, 29.0%) rates. The objective of this investigation was to directly compare the long-term clinical complication rates of VFNFs repaired by crossed (Alpha fixation) or parallel screws in non-geriatric patients. Patients and Methods:We conducted a retrospective comparative study of VFNFs in patients ( < 60 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Previous study has suggested that Pauwels screws provide a higher holding force because the bone quality around the femoral calcar is superior to the bone quality around the Ward's triangle of the femur. [29] However, in our study, we assigned the same material parameter to the cancellous bone, suggesting that other possible explanations for the biomechanical advantage of FCS are also important. We speculate that the additional Pauwels screws share the stress on the remaining three parallel screws compared to the TCS, thus reducing the stress concentration on each screw.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous study has suggested that Pauwels screws provide a higher holding force because the bone quality around the femoral calcar is superior to the bone quality around the Ward's triangle of the femur. [29] However, in our study, we assigned the same material parameter to the cancellous bone, suggesting that other possible explanations for the biomechanical advantage of FCS are also important. We speculate that the additional Pauwels screws share the stress on the remaining three parallel screws compared to the TCS, thus reducing the stress concentration on each screw.…”
Section: Discussionmentioning
confidence: 82%
“…Xiangyu Xu, et al analyzed 102 patients with FNF treated with TCS and FCS and reported no signi cant difference in the rate of internal xation failure in the treatment of Garden III and IV fractures, but FCS reduced femoral neck shortening and improved the postoperative Harris hip score [24]. Dajun Jiang, et al reported that FCS had a signi cantly lower rate of femoral neck shortening (8.3% vs. 28.9%) than that of TCS [29].…”
mentioning
confidence: 99%
“…In clinical practice, surgeons should be aware of the inherent high risks of complications in fractures with unstable inclination angles, and handle these patients more prudently and schedule closer follow-ups. Because of the unstable nature, apart from achieving an acceptable reduction, a more biomechanically beneficial fixation strategy such as sliding hip screws ( Bhandari and Swiontkowski, 2017 ; Augat et al, 2019 ), Buttress plate ( Zhan et al, 2020 ; Jiang et al, 2021c ), Alpha fixation ( Jiang et al, 2021b ; Jiang et al, 2021c ) or the Tragon locking plate system ( Bliven et al, 2020 ) were more recommended for these fractures compared with traditional three parallel screws. However, clinical evidence of the optimal internal fixation selection for the real unstable femoral neck fractures is still absent.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical outcomes have demonstrated the approach's efficiency for bone healing [5,6], the surgical failure rate for vertical FNFs remains high [7,8]. Surgeons have attempted to modify multiple-screw fixation with regard to the direction, number of screws and configuration to improve its biomechanical properties [9][10][11]. However, the role of screws type on fixation effects is unclear, and the question of how the use of different types of screws affects the vertical FNF's biomechanical stability is still open and has increasingly attracted attention [12,13].…”
Section: Introductionmentioning
confidence: 99%